ANALISIS LAPORAN KEUANGAN DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA PERUSAHAAN SUBSEKTOR LOGAM DASAR BESI DAN BAJA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurhadi Kamaluddin; Aprilia Andiini (Program Studi Akuntansi, Universitas Kuningan, 2022)
Investment is becoming a trending thing at this time, the increasingly widespread level of development in the millennial era demands to continue to drive a more advanced economy. Especially with the existence of an uncertain problem during the Covid 19 era, the economy at that time was destroyed. Therefore, potential investors will choose the right company as an investment medium. One of the investments that many potential investors also make is stock investment. The place for potential investors to see stock movements or regarding a company's financial position is on the IDX. The importance of investment in improving welfare in the future encourages us to fully understand how the right analysis can reduce the high level of risk and of course with a good level of future cash flow. In this study the authors use the object of financial reports for 2019 – 2021 for iron and steel base metal subsector companies listed on the IDX. The method used is growth analysis and cross sectional analysis using ratios. The results in this study will show how the level of financial management in a company to investment decision making. Determination of appropriate or not feasible in a company will be determined on the final scoring of the weighted value than the average of other companies. And of the eight base metal iron and steel sub-sector companies listed on the IDX, PT Betonjaya Manungal Tbk, PT Liomesh Prima Tbk, and PT Saranacentral Bajaratma have the highest final score level than the other averages and are companies that are worthy of investment media, which means that the company It has a good level of future cash flow and low riskKeywords: investment, analysis of financial statements, financial reports